الإعلام بين الحرية والمسؤولية الاجتماعية - • بلقندوز ريم; • عوينة فوزي; - أ. رابحي سليمة (جامعة محمد بوضياف -المسيلة, 2024)
يرتبط الإعلام في العصر الحديث ارتباطا وثيقا بدوره في المجتمع وعلاقته بالفرد المتلقي، كون هذا الأخير يعتبر الحلقة الأخيرة والمهمة في عناصر العملية الاتصالية، وكيفيات استقباله للرسالة الإعلامية ومدى استيعابه لها وتناغمه مع مضمونها من عدمه، وهو ما اتجه بالفكر الاجتماعي إلى ربط نشاط وسائل الإعلام بالمجتمع من خلال تحميله مسؤولية نقل الواقع من قبل وسائل الإعلام باختلافها أخذين بعين الاعتبار مسؤولية تماشي ما ينشر ويذاع من مضامين إعلامية مع ذلك الواقع، أي عدم استخدام مصطلح الحرية كمفهوم مطلق مثلما حدث في النظم الإعلامية والاتصالية الليبرالية التي أطلقت العنان لممارسة الحرية الإعلامية حتى تم تمييعه من قبل الصحفيين، ما نجم عنه فوضى إعلامية كبيرة وتناقض بين وسائل الإعلام والرأي العام (الجمهور). The media in the modern era is closely linked to its role in society and its relationship with the recipient individual, since the latter is considered the last and important link in the elements of the communication process, and the ways in which he receives the media message and the extent of his absorption of it and his harmony with its content or not, which is what led social thought to link the activity of the media with society. By holding him responsible for conveying reality by the various media, taking into account the responsibility for the media content that is published and broadcast to be consistent with that reality, that is, not using the term freedom as an absolute concept, as happened in liberal media and communication systems. Which unleashed the practice of media freedom until it was diluted by journalists, resulting in great media chaos and a contradiction between the media and public opinion (the public). : media, freedom, social responsibility, public. الاعلام، الحرية، المسؤولية الاجتماعية، الجمهور.